The Impact of Advances in Digital Technology on Education and Moral Character Among Students and College Students - Nisa Aulia Fadhilah; Septia Nur Fadhilah; Winda Nor Hidayah; Muhamad Faqih Igbal; Danisa Febrianasari; Septa Nur Rahman; Puti Ellyani Tri Agustin; Abyan Meidatama Baskara; Arif Widagdo (Journal of Contemporary Pedagogy and Learning Science, 2026)
Advances in digital technology have significantly transformed educational systems by expanding access to learning resources, supporting flexible learning environments, and improving instructional and administrative efficiency. A qualitative library research approach was employed to examine the implications of digital technology for education and the moral character of students and college students. Data were collected from scholarly books, journal articles, and relevant academic publications and analyzed through qualitative content analysis and descriptive-analytical techniques. The findings indicate that digital technology promotes autonomous learning, collaboration, digital literacy, and personalized learning experiences through artificial intelligence and online platforms. At the same time, several challenges emerge, including digital dependency, information overload, cyberbullying, ethical misconduct in digital communication, and academic integrity issues associated with the misuse of generative artificial intelligence. The analysis suggests that technological advancement should be accompanied by the strengthening of digital literacy, character education, and ethical awareness. Sustainable educational outcomes require collaboration among educators, parents, and educational institutions to ensure that technology contributes positively to both intellectual development and moral character formation.